Importance of Direct Antiglobulin Test (DAT) in Cord Blood: Causes of DAT (+) in a Cohort Study - Serena Valsami; Marianna Politou; Τheodora Boutsikou; Despina Briana; Milena Papatesta; Ariadne Malamitsi-Puchner (Elsevier, 2015)
The direct antiglobulin test (DAT) is the cornerstone of the diagnosis of hemolytic disease of the newborn (HDN). The aim of this study was to review the incidence and causes of positive DAT in cord blood in relation to development of HDN. Methods: We retrospectively reviewed all results of DAT, which is routinely performed in cord blood samples, along with the laboratory and infants' medical records. Results: DAT was positive in 70/2695 (2.59%) cases. In 64/70 (91.43%) cases, DAT positivity was attributed to ABO incompatibility. There were 50/218 (22.93%) DAT (+) cases in the A/O group and 13/97 (13.40%) cases in the B/O group (p = 0.0664). Two DAT (+) cases were attributed to maternal alloimmunization (anti-Fya and anti-JKb, respectively), and one to maternal IgG autoantibodies that developed after methyldopa treatment. Among the 70 DAT (+) cases, 30 (42.86%) cases required phototherapy with no difference between the A/O and B/O groups. The duration of phototherapy in the B/O group was significantly longer than in the A/O group (p = 0.024). There was a trend of correlation of increasing strength of DAT positivity with phototherapy need. No false positive DAT case was detected. Conclusions: Although ABO incompatibility remains the main reason of DAT (+), other causes (e.g., alloimmunization, drugs) should also be explored. The relevant impact of DAT (+) on HDN development should be considered.